The efficacy of a brief supportive psychodynamic therapy in treating anxious-depressive disorder in daily hospital - Brajković, Lovorka (Array, 2009)
Abstract: Study objective is to determine the efficacy of brief supportive psychodynamic therapy in treating anxious-depressive disorder in Daily hospital wwithin the Psychological Medicine Clinic. The study comprised a total of 45 male subjects, in which an admission to the Daily Hospital was indicated. On the occasion of the hospital admission, as well as following the completion of a one month-lasting partial hospitalisation within the Daily Hospital, the subjects had undergone testing using a number of psychological instruments. There weren’t established statistically significant differences in clinical presentations of the treated patients. A partial, one month-lasting hospitalisation, did not yield any changes in clinical presentation an anxious-depressive disorder. Due to the fact that this psychotherapeutic method should be applied for quite some time in order to yield results, and is not expected to be effective in a close range, a one-month lasting treatment is definitely not long enough to be effective